Effects of various curing methods on the compressive strength and microstructure of blast furnace slag-fly ash-based cementitious material activated by alkaline solid wastes. (28th November 2022) - Guo, Weichao; Zhao, Qingxin; Sun, Yijia; Xue, Caihong; Bai, Yanying; Shi, Yuxuan
Highlights: Optimal curing method for a type of solid wastes-based binder was identified. Curing at 75 ℃ for 12 h was proved to be the optimal heat-curing (HC) method. HC accelerates the generation of gel and crystals, promoting the early strength. Proper HC can improve the consolidation rate of Cl - and reduce the porosity. Excessive HC causes proliferation of cracks and porosity in the matrix, leading to strength retrogression. Abstract: The large-scale stacking of alkaline industrial solid wastes such as soda residue (SR) and calcium carbide residue (CCR) has caused serious environmental problems. Therefore, a new type of cementitious material was developed in our previous study by using SR-CCR synergistically activated blast furnace slag (BFS)-fly ash (FA), which abbreviated as SCBF. This paper further studied the effects of various curing methods on the compressive strength and microstructure of SCBF, which was expected to provide guidance for its application in the field of non-reinforced products such as baking-free brick. The results show that the optimal curing scheme was heat curing at 75 °C for 12 h. The optimal scheme significantly promoted an early hydration reaction and provided the 3d/28d strength values of 16.4/24.7 MPa, exceeding those of room-temperature (RT) sealed curing and water curing by 154/24.5 % and 264/31 %, respectively. Besides, the optimal scheme accelerated the formation of CSH gel, Hydrotalcite (6MgO·Al2 O3 ·CO2 ·12H2 O), Hydrocalumite (3CaO·Al2 O3 ·CaCl2 ·10H2 O), and other crystal products, as well as increased the consolidation rate of chlorine ion from 37.9 % (in RT sealed curing) to 64.3 %. These hydration products were evenly distributed, effectively filling the pores and reducing the macroporosity from 9.30 (in RT sealed curing) to 1.54 %, thus improving the early and later-age strength. Too high curing temperature (exceeding 75 ℃) or prolong heat curing period (exceeding 12 h) would cause microstructure deterioration, significantly increase the number of macropores and microcracks in the matrix, ultimately leading to strength retrogression.